Performance comparison of different control strategies for the regulation of DC-DC negative output super-lift luo-converter - Hassan Jassim Motlak; Ahmed S. Rahi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In last years, dc-dc converters solve the most issues in the industrial application in the area of power electronics, especially renewable energy, military applications and affiliated engineering developments. They are used to convert the DC input that unregulated to regulated output perhaps larger or smaller than input according to the type of converters. This paper presents three primary control method used for negative output Super lift Luo DC-DC converter. These methods include a Voltage mode control (VMC), Current mode control (CMC), and Sliding mode control (SMC). The goal of this article is to study and selected an appropriate and superior control scheme for negative DC-DC converters. The simulation results show the effectiveness of Sliding mode control for enhancing the performance of the negative dc-dc converter. Also, this method can keep the output voltage constant under load conditions. simulation results obtained by the MATLAB/Simulink environment.